2019
DOI: 10.31686/ijier.vol7.iss11.2012
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate the quality of suppliers in a PIM`s Company X

Abstract: The research was carried out in Company X that operates in the electronics industry at Manaus Industrial Pole (PIM). The objective is to propose a system of indicators to evaluate the quality of suppliers, in order to enable the relationship`s continuous improvement among company and its suppliers. Based in the collection and analyzed data, it was possible to identify six successful cases of suppliers' quality assessment indicators system, which permitted to propose, in partnership with managers, a model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They found significant level of correlation between CaI I and NaI absorption and confirm that NaI D1&D2 lines can be used as an activity indicator in stars with low level of activity. While Gomes da Silva et al (2011) asserted that index manipulating HeI variability is a poor indicator of stellar activ- ity, Saar et al (1997) claimed, they have found correlation between HeI D3 and CaI I H&K variation. Solar-type spectra are also covered with molecular absorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found significant level of correlation between CaI I and NaI absorption and confirm that NaI D1&D2 lines can be used as an activity indicator in stars with low level of activity. While Gomes da Silva et al (2011) asserted that index manipulating HeI variability is a poor indicator of stellar activ- ity, Saar et al (1997) claimed, they have found correlation between HeI D3 and CaI I H&K variation. Solar-type spectra are also covered with molecular absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Activity in solar-type stars is relatively old subject in astrophysics which has been addressed by many authors (Wilson 1968(Wilson , 1978Saar et al 1997;Santos et al 2000;Diaz et al 2007;Boisse et al 2009;Cincunegui et al 2007;Lovis et al 2011;Gomes da Silva et al 2011). In late 60's Wilson (1968Wilson ( , 1978 introduced an index, S, to measures the CaI I H&K lines emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation